A post‐GWAS confirming the SCD gene associated with milk medium‐ and long‐chain unsaturated fatty acids in Chinese Holstein population. (11th March 2016) - Li, C.; Sun, D.; Zhang, S.; Liu, L.; Alim, M. A.; Zhang, Q.
Summary: The s tearoyl‐CoA desaturase (delta‐9‐desaturase) gene encodes a key enzyme in the cellular biosynthesis of monounsaturated fatty acids. In our initial genome‐wide association study (GWAS) of Chinese Holstein cows, 19 SNPs fell in a 1.8‐Mb region (20.3–22.1 Mb) on chromosome 26 underlying the SCD gene and were highly significantly associated with C14:1 or C14 index. The aims of this study were to verify whether the SCD gene has significant genetic effects on milk fatty acid composition in dairy cattle. By resequencing the entire coding region of the bovine SCD gene, a total of six variations were identified, including three coding variations (g.10153G>A, g.10213T>C and g.10329C>T) and three intronic variations (g.6926A>G, g.8646G>A and g.16158G>C). The SNP in exon 3, g.10329C>T, was predicted to result in an amino acid replacement from alanine (GCG) to valine (GTG) in the SCD protein. An association study for 16 milk fatty acids using 346 Chinese Holstein cows with accurate phenotypes and genotypes was performed using the mixed animal model with theproc mixed procedure insas 9.2. All six detected SNPs were revealed to be associated with six medium‐ and long‐chain unsaturated fatty acids ( P = 0.0457 to P < 0.0001), specifically for C14:1 and C14 index ( P = 0.0005 to P < 0.0001). Subsequently, strong linkage disequilibrium ( D ′ = 0.88–1.00) was observed among all six SNPs in SCD and the five SNPs (rs41623887, rs109923480, rs42090224, rs42092174 and rs42091426) within the 1.8‐Mb region identified in our previous GWAS, indicating that the significant association of the SCD gene with milk fatty acid content traits reduced the observed significant 1.8‐Mb chromosome region in GWAS. Haplotype‐based analysis revealed significant associations of the haplotypes encompassing the six SCD SNPs and one SNP (rs109923480) in a GWAS with C14:1, C14 index, C16:1 and C16 index ( P = 0.0011 to P < 0.0001). In summary, our findings provide replicate evidence for our previous GWAS and demonstrate that variants in the SCD gene are significantly associated with milk fatty acid composition in dairy cattle, which provides clear evidence for an increased understanding of milk fatty acid synthesis and enhances opportunities to improve milk‐fat composition in dairy cattle.